Roztochia`s transport in the context of recreational development of the region - Бордун, О. Ю.; Грицевич, В. С. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2016)
The history of Ukrainian Roztochia’s transport development includes its transport-geographical position, natural-geographical, historical, demographical, economical and recreational conditions. Roztochia’s transport-geographical situation can be assessed as the advantageous with the developed borderland infrastructure and transport network. Natural-geographical pre-conditions are ambiguous and create some problems of Roztochia’s transport networks. These problems arise from the hilly relief. History of Roztochia’s transport development embraces a large period, including times of Kievan Rus, Kingdom of Galicia–Volhynia, Austrian monarchy, ХХ century and modernity. Demographic pre-conditions of Roztochia’s transport developemnt are determined by the near location of metropolis – a regional center of Lviv, and district centers – Zhovkva and Yavoriv. The economic pre-conditions for the development of transport are determined by the orientation of Roztochia on transborder transportations. Recreational pre-conditions for the development of transport arising from the presence of the renowned spa centers (Shklo, Nemyriv, Bryukhovychi), tourist and pilgrimage centers (Zhovkva, Krekhiv, Stradch), and in recent years the areas of green tourism. Roztochia’s region is characterized by a relatively good transport networks between the towns of the region: Zhovkva and Yavoriv, a small town Dubliany, Rawa-Ruska, Kulykiv and Mageriv as well as townships: Ivano-Frankove, Krakovets, resorts of Shklo, Nemyriv, although the conditions of peripheral highways are not satisfactory. The network of highways includes the roads of all types (international, national, regional, territorial and local). Alongside international transport corridors pass through Roztochia. The main centers of transport-logistic activity in freight transportations are Malekhiv, Zhovkva, Novo-Yavorivsk, Yavoriv. The biggest working international border-check points are "Rava-Ruska" and "Krakivets".